KNOWLEDGE RELATIONSHIPS WITH BEHAVIOR PREVENTION OF TRANSMISSION OF PULMONARY TB PATIENTS TO THE FAMILY AT THE WORKING AREA OF THE DISTRICT HEALTH CENTERS NGAMBON BOJONEGORO: KNOWLEDGE RELATIONSHIPS WITH BEHAVIOR PREVENTION OF TRANSMISSION OF PULMONARY TB PATIENTS TO THE FAMILY AT THE WORKING AREA OF THE DISTRICT HEALTH CENTERS NGAMBON BOJONEGORO - Emawati, Dyah (Well Being, 2017)
Some patients with pulmonary tuberculosis has been observed in Ngambon Health Center, showed that patients is less understanding of the knowledge and prevention behaviors. The high number of patients with pulmonary TB comes largely from the socioeconomic low groups and education low levels. The purpose of this study was to determine Knowledge Relationships with Behavior Prevention of Transmission of Pulmonary TB Patients to the Family at The Working Area Of The District Health Centers of Ngambon Bojonegoro. The study design used is correlation analytic with cross sectional approach, the population in this study were 32 patients with pulmonary TB positive AFB in Ngambon Health Centers, with 25 people sample. The sampling is done by purposive sampling. Analysis of data using statistical test Spearman rho. Spearman rho test results statistically with α = 0.05 ρ = 0.000 obtained results, then ρ < α Ho refused and H1 accepted which means there the relationship of knowledge to transmission prevention behavior with pulmonary TB to the family in the health center of Ngambon Bojonegoro 2015. Based on the above, it is expected all pulmonary TB patients get information about the knowledge of good behavior to patients with pulmonary tuberculosis in order to prevent transmission.